MULTI LEVEL MARKETING SHARIA - Herry Syahbannuddin Nasution; Andri Soemitra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Sharia MLM Business is dependent business on standard sharia. Study this use method study literature study and approach descriptive qualitative that is content analysis of papers from the Google Scholar database. Selected paper in this review originated from search on the Google Scholar database with the keywords "multi level marketing" MLM and Islam or Sharia and fiqh and fiqh period 2015 to 2022. Search process use help Publish or Perish application. On Step first writer to do search for papers in the Google Scholar database with the keyword “multilevel marketing” found 211 matching papers with keywords search. Explained that article journal of 26 papers summarized into 7 topics discussion tree with the findings described among others: Sharia MLM in Islamic view ( Sharia ) there are 13 papers, Settings compensation Sale Direct tiered Sharia (PLBS) in Indonesia there are 7 papers, Products Multi-Level Marketing Hajj and Umrah there is 1 paper, MLM in Perspective Fiqh scholars there is 1 paper, Concept on Shari'ah MLM Practice there is 1 paper, Akad Ju’alah on Sharia MLM agent there are 2 papers and Overview Analytic and Criticism: Concept and Practice Multi Level Marketing (MLM) Syari'ah in Indonesia there is 1 paper. Management sharia MLM business set According to the MUI Fatwa, namely: in the DSN-MUI Fatwa No. 75/DSN-MUI/VII/2009 regarding Guidelines Sale Direct tiered Sharia.